Melodi Savanna: Membangun Basic Listening Skill Melalui Musik Anak-Anak Di Madrasah Ibtidaiyah - Abdul Syahid; Syahrul Mubaroq; Tiara Nur Fatimah Almadani; Siti Nurrahmah; Muliana Setia Hapsari; Ayu Putriana; Muhamad Noor Fauzan (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2024)
This community service initiative responds to issues related to listening skills and adopts a planned approach to achieve optimal learning goals. The focus of this intervention is on introducing an innovative method called "Savanna Melody," with the aim of enhancing children's listening abilities through a musical approach. The primary objective of the service activity is to make a positive contribution by increasing the interest and understanding of English among children. The implementation method involves interactive sessions that integrate audio and visual elements. The observed impacts include increased active participation and comprehension of the material, indicating the potential for fundamental changes in the English language learning approach within the context of the school.